Autism Spectrum Disorders and Epilepsy - Kika, Migena; Merkaj, Venetike; Rada, Artur (Richtmann Publishing, 2012)
Epileptic seizures are frequent in children with ASD with a reported prevalence between 7% and 46%. These figuresare higher than those reported for the normal pediatric population but the true prevalence remains uncertain because studiesexamining this have included comorbid conditions.Aim: Study the prevalence of epilepsy in children diagnosed with ASD.Methods: Retrospective study of 30 children diagnosed with ASD in the National Center for Growth, Development andRehabilitation of Children. The clinical history and electroencephalograms of these children were reviewed. The children werefrom 2 years old until 8 years old.Results: 7 out of 30 children diagnosed with ASD were also diagnosed with epilepsy orabnormal electroencephalograms with a prevalence of 23%. These children showed more profound intellectual impairment andregression in cognitive development than those with ASD, but no epilepsy. Conclusion: ASD in early childhood is associated withhigh rate of epilepsy . These findings suggest that neurological investigative techniques such as EEG should be consideredduring evaluation of children with ASD with more impaired cognition.